The independent high rate algal pond as a unit operation in tertiary wastewater treatment - Clark, Stewart James (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2002)
The development of the High Rate Algal Pond (HRAP) as an independent tertiary treatment unit operation for phosphate and nitrate removal is reported. A novel Integrated Algal Ponding System (lAPS) design is proposed for nutrient removal from the effluents of both a conventional domestic sewage treatment plant and from an Advanced Integrated Wastewater Ponding System (AIWPS). The viability of an independently operated HRAP has been identified and termed the Independent High Rate Algal Pond (l-HRAP). A 500 mÂ² pilot 1- HRAP was operated in such a way as to facilitate the precipitation of calcium phosphate, known to be controlled by pH (greater than 9.4) and resulting in final phosphate levels of less than 1 mg.Lâ »Â¹ as P0â‚„-P. The incorporation of the I-HRAP into a denitrification process was also investigated. Continuously fed column reactors, utilising algal biomass as a carbon source, showed that the heterotrophic bacterial community dominant in the anaerobic algal sludge were denitrifying the nitrate in the feed. It was demonstrated that as the cultures were stressed (using increased nitrate concentrations, anaerobiosis and light starvation) total polysaccharide (TPS) concentrations increased, with a notable increase 111 the exopolysaccharide (EPS) fraction. These experiments corroborated the hypothesis that harvested microalgal biomass can be manipulated to produce, and release, exopolymeric substances under stress conditions, and which may serve as carbon source for denitrification. In both batch flask studies and in laboratory-scale reactor systems, harvested microalgal biomass from an HRAP was shown to produce exopolymeric substances under stress conditions. Initial high loading-rates of greater than 20 mg.Lâ »Â¹ NOâ‚ƒ-N resulted in double the amount of exopolysaccharide production than in flasks with initial low loading-rates (less than 5 mg.Lâ »Â¹ NOâ‚ƒ-N). Making use of an upflow anaerobic sludge blanket-type degrading-bed reactor, and an anaerobic, flooded trickle filter (ANTRIC) receiving HRAP effluent, the relationship between denitrification and the changes in polysaccharide content was investigated. This phenomenon has considerable beneficial implications in biological wastewater treatment systems where high nitrate concentration in the final effluent is a potential mitigating factor. Identification of the heterotrophic bacteria active in the denitrification process was attempted. This study presents a first report on the development and operation of the I-HRAP and has been followed by a technical-scale pilot plant evaluation of the process in the tertiary treatment of domestic wastewaters.
Keywords: Algae -- Biotechnology; Sewage -- Purification -- Biological treatment